MENGURAI KONSEP PENDEKATAN HERMEUNITIKA DAN FENOMENOLOGIS DALAM KAJIAN ISLAM: SEBUAH STUDI LITERATUR [UNRAVELING THE CONCEPT OF HERMENEUTICAL AND PHENOMENOLOGICAL APPROACHES IN ISLAMIC STUDIES: A LITERATURE STUDY] - Rahmat, Hayatul Khairul; Hasbi, M. Zidny Nafi’ (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2024)
This study aims to analyze the hermeneutic and phenomenological approaches in Islamic studies. This study uses a library method. The application of hermeneutic and phenomenological methods in Islamic studies involves an interpretive approach to understanding and interpreting sacred texts and religious phenomena. In this study, researchers will use practical steps to apply methods such as in-depth text analysis, historical, social, and cultural context tracing, and the application of hermeneutic and phenomenological principles.